2016
DOI: 10.1016/j.ndteint.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic array imaging through an anisotropic austenitic steel weld using an efficient ray-tracing algorithm

Abstract: Ultrasonic inspection of austenitic welds is challenging due to their highly anisotropic and heterogeneous microstructure. The weld anisotropy causes a steering of the ultrasonic beam leading to a number of adverse effects upon ultrasonic array imagery, including defect mislocation and aberration of the defect response. A semi-analytical model to simulate degraded ultrasonic images due to propagation through an anisotropic austenitic weld is developed. Ray-tracing is performed using the A* path-finding algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Beamforming of focusing problem is performed by exciting transducer elements with different time delays. Delay from source S (phased array element) to target T (defect) was calculated using conventional methods and trigonometric functions with respect to angles or by Fermat principle to express as the shortest path problem [8]. Proposed method focusing is expressed by semi analitical fashion with coordinate transformation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Beamforming of focusing problem is performed by exciting transducer elements with different time delays. Delay from source S (phased array element) to target T (defect) was calculated using conventional methods and trigonometric functions with respect to angles or by Fermat principle to express as the shortest path problem [8]. Proposed method focusing is expressed by semi analitical fashion with coordinate transformation.…”
Section: Methodsmentioning
confidence: 99%
“…Otherwise, optimization formula, which includes basis function, needs to be derived. It is not worth to derive it and for optimization of (7) and (8) iterative root finding method can be used from sage software [11]. The example below is calculated using iterative root finding algorithm method with the grid in the same way for line and B-splines.…”
Section: Examplementioning
confidence: 99%
See 1 more Smart Citation
“…This principle can be effectively used with efficient shortest path-finding algorithms popular from the origins of computer science. Zhang et al [11] suggested using various incarnations of the Dijkstra method to model ultrasound in welds, which was further studied in more detail in [19,20]. The present model draws from those contributions but with some modifications to improve efficiency.…”
Section: Forward Modelmentioning
confidence: 99%
“…For defects on the far-side of the sample from the transducer, bulk ultrasound waves can be used for inspection. Where only one side of the sample is accessible, standard inspection may use time of flight diffraction, or phased array techniques [14,15]. For a simple inspection procedure, a modified version of through-transmission using an angle beam probe can be used, where a wave is transmitted into a sample and the blocking of the wave by a far-side defect is imaged [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%